Perceptual vowel contrast reduction in Australian English /l/-final rimes. Issue 1 (12th April 2021) - Szalay, Tünde; Benders, Titia; Cox, Felicity; Proctor, Michael
Abstract : In Australian English rimes, coarticulation between coda /l/ and its preceding vowel has the potential to attenuate cues that contribute to phonological vowel contrast. Therefore, vowel-/l/ coarticulation may increase ambiguity between prelateral vowels. We used a vowel identification task to test the effect of vowel-/l/ coarticulation on vowel disambiguation in perception. Listeners categorized vowels in /hVd/ and /hVl/ contexts. Results showed reduced accuracy of vowels before coda /l/ compared to coda /d/, showing that coda /l/ increases vowel disambiguation difficulty. In particular, reduced perceptual contrast was found for the rime pairs /ʉːl-ʊl, æɔl-æl/ and /əʉl-ɔl/ (e.g., fool-full, howl-Hal, dole-doll ). A second experiment tested the effect of reduced perceptual contrast on word recognition. Listeners identified minimal pairs contrasting key vowel pairs in the /CVl/ and /CVd/ contexts. Reduced accuracy and increased response time in /l/ contexts shows that coda /l/ hinders listeners' ability to identify vowels. The implications of reduced perceptual vowel contrast for compensation for coarticulation and sound change are discussed.